A Model of Comprehensive Habits with Psychological Effects of Work Effort - GURDGIEV, CONSTANTIN (My University, 2004)
This paper develops a neoclassical growth model under the assumption of comprehensive habits that incorporate both consumption and labour supply decisions of the households. We show that in presence of comprehensive habits, households will supply more labour than in case of no habits. In addition we consider two possible psychological links between the wage rate and the habits mechanism. We distinguish between satisfaction effect of work effort and status effect of work effort by creating an explicit positive and negative links between higher wages and the importance of labour supply relative to consumption in determination of comprehensive habits stock. We analyse the different results obtained in the model under this distinction.
PUBLISHED
Keywords: Economics; habits; consumption; labour supply